A PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MULTI SARANA AGRO MANDIRI (MSAM) KOTABARU: MANAJEMEN SUMBER DAYA MANUSIA - Saskiah; Hairul; Hasanah, Nurul (Jurnal Ilmiah Ekonomi Bisnis, 2024)
This research aims to analyze (1) motivation influences employee performance at PT. Multi Sarana Agro Mandiri (MSAM) Kotabaru, (2) work discipline influences employee performance at PT. Multi Sarana Agro Mandiri (MSAM) Kotabaru, (3) motivation and work discipline influence employee performance at PT. Multi Sarana Agro Mandiri (MSAM) Kotabaru. This research design is quantitative research and is survey research using a questionnaire. The research population was employees of PT. Multi Sarana Agro Mandiri (MSAM) Kotabaru and a sample of 40 respondents with Multiple Linear Regression data analysis. The research results show (1) motivation partially has a significant effect on employee performance at PT. Multi Sarana Agro Mandiri (MSAM) Kotabaru (2) work discipline partially has a significant effect on employee performance at PT Multi Sarana Agro Mandiri (MSAM) Kotabaru (3) work motivation and discipline simultaneously has a significant effect on employee performance at PT Multi Sarana Agro Mandin (MSAM) Kotabaru. Keywords : Motivation, Work Discipline, Employee Performance